Body weight-supported treadmill training vs. overground walking training for persons with chronic stroke: a pilot randomized controlled trial. (September 2014) - Combs-Miller, Stephanie A; Kalpathi Parameswaran, Anu; Colburn, Dawn; Ertel, Tara; Harmeyer, Amanda; Tucker, Lindsay; Schmid, Arlene A
Objective: To compare the effects of body weight-supported treadmill training and overground walking training when matched for task and dose (duration/frequency/intensity) on improving walking function, activity, and participation after stroke. Design: Single-blind, pilot randomized controlled trial with three-month follow-up. Settings: University and community settings. Subjects: A convenience sample of participants ( N = 20) at least six months post-stroke and able to walk independently were recruited. Interventions: Thirty-minute walking interventions (body weight-supported treadmill training or overground walking training) were administered five times a week for two weeks. Intensity was monitored with the Borg Rating of Perceived Exertion Scale at five-minute increments to maintain a moderate training intensity. Main Measures: Walking speed (comfortable/fast 10-meter walk), walking endurance (6-minute walk), spatiotemporal symmetry, and the ICF Measure of Participation and ACTivity were assessed before, immediately after, and three months following the intervention. Results: The overground walking training group demonstrated significantly greater improvements in comfortable walking speed compared with the body weight-supported treadmill training group immediately (change of 0.11 m/s vs. 0.06 m/s, respectively; p = 0.047) and three months (change of 0.14 m/s vs. 0.08 m/s, respectively; p = 0.029) after training. Only the overground walking training group significantly improved comfortable walking speed ( p = 0.001), aspects of gait symmetry ( p = 0.032), and activity ( p = 0.003) immediately after training. Gains were maintained at the three-month follow-up ( p < 0.05) for all measures except activity. Improvements in participation were not demonstrated. Conclusion: Overgound walking training was more beneficial than body weight-supported treadmill training at improving self-selected walking speed for the participants in this study.